Aerobic Exercise Recommendations to Optimize Best Practices in Care After Stroke: AEROBICS 2019 Update. Issue 1 (9th October 2019) - MacKay-Lyons, Marilyn; Billinger, Sandra A; Eng, Janice J; Dromerick, Alex; Giacomantonio, Nicholas; Hafer-Macko, Charlene; Macko, Richard; Nguyen, Emily; Prior, Peter; Suskin, Neville; Tang, Ada; Thornton, Marianne; et al.
Abstract: Most stroke survivors have very low levels of cardiovascular fitness, which limits mobility and leads to further physical deconditioning, increased sedentary behavior, and heightened risk of recurrent stroke. Although clinical guidelines recommend that aerobic exercise be a part of routine stroke rehabilitation, clinical uptake has been suboptimal. In 2013, an international group of stroke rehabilitation experts developed a user-friendly set of recommendations to guide screening and prescription—the Aerobic Exercise Recommendations to Optimize Best Practices in Care after Stroke (AEROBICS 2013). The objective of this project was to update AEROBICS 2013 using the highest quality of evidence currently available. The first step was to conduct a comprehensive review of literature from 2012 to 2018 related to aerobic exercise poststroke. A working group of the original consensus panel members drafted revisions based on synthesis. An iterative process was used to achieve agreement among all panel members. Final revisions included: (1) addition of 115 new references to replace or augment those in the original AEROBICS document, (2) rewording of the original recommendations and supporting material, and (3) addition of 2 new recommendations regarding prescription. The quality of evidence from which these recommendations were derived ranged from low to high. The AEROBICS 2019 Update should make it easier for clinicians to screen for, and prescribe, aerobic exercise in stroke rehabilitation. Clinical implementation will not only help to narrow the gap between evidence and practice but also reduce current variability and uncertainty regarding the role of aerobic exercise in recovery after stroke.